Psychometric evaluation of purchase intention and actual purchase behaviour towards halal bakery products using rasch analysis - Nurzulain Z.,; Zuraini M.I.,; Norhidayah A.,; Muhammad Afiq M., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although bakery products are a hit among Malaysian consumers, questions still arise on the halal seal of the ingredients used. Therefore, producing halal bakery products can be an option to fulfill the needs of consumers. To further explore the intention and to examine their purchase behaviour, the theory of planned behaviour (TPB) was applied. Hence, this study examined the psychometric properties of an instrument used to determine both purchase intention and the actual purchase behaviour of halal bakery products among Muslim and non-Muslim consumers. The questionnaire was distributed to 70 respondents who had purchased bakery products at any bakery shops in Klang, Selangor. The data were subjected to Rasch analysis using Bond & Fox (2nd Version) software program for fit statistics, response category performance, unidimensionality, and a Wright map. The different item functioning (DIF) analysis was employed to detect bias between Muslim and nonMuslim consumers. The results indicated that all items that fit the Rasch model were unidimensional. However, one item was regarded as a difficult item, while three items had a religious bias. In conclusion, the instrument was valid and reliable to be used for Muslim and non-Muslim consumers.